2021
DOI: 10.1177/22785337211018313
|View full text |Cite
|
Sign up to set email alerts
|

Can Workplace Fun Moderate Organizational Identification and Job Satisfaction Relationship

Abstract: Job satisfaction is critical to the changing and growing challenges of the service sector. The present research study investigates the moderation effect of workplace fun on the relationship between organizational identification (OID) and job satisfaction. The sample was 220 frontline employees in 57 hotels in Nigeria. We found that OID positively influenced job satisfaction. Additionally, workplace fun moderated the effect of OID onjob satisfaction. The findings suggest that organizational leaders can use fun … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 92 publications
0
7
0
Order By: Relevance
“…And in particular, we operationalized well‐being by means of two indicators that are of opposite valence: happiness (on the positive side) and personal stress (on the negative side). According to the aforementioned rationale (Hameed, Ijaz, & Sabharwal, 2021; Li, Fan, & Zhao, 2015; Ugheoke, Mashi, & Isa, 2021), we expected a positive relationship between organizational outcomes and personal well‐being.…”
Section: Turnover Intention and Job Satisfaction As Mediatorsmentioning
confidence: 99%
“…And in particular, we operationalized well‐being by means of two indicators that are of opposite valence: happiness (on the positive side) and personal stress (on the negative side). According to the aforementioned rationale (Hameed, Ijaz, & Sabharwal, 2021; Li, Fan, & Zhao, 2015; Ugheoke, Mashi, & Isa, 2021), we expected a positive relationship between organizational outcomes and personal well‐being.…”
Section: Turnover Intention and Job Satisfaction As Mediatorsmentioning
confidence: 99%
“…In this regard, fun is often recognized as a tool to increase an individual's satisfaction and commitment (Everett, 2011). Although workplace fun helps generate favourable organizational outcomes (Ugheoke et al, 2021) at an individual level, the impact may not be We argue that employees' attitude towards fun is an important aspect in assessing their sense of life satisfaction. Following positive psychology, this study shows that the psychological motivational process (engagement) is an underlying mechanism through which workplace fun can influence life satisfaction.…”
Section: Discussionmentioning
confidence: 91%
“…In this regard, fun is often recognized as a tool to increase an individual’s satisfaction and commitment (Everett, 2011). Although workplace fun helps generate favourable organizational outcomes (Ugheoke et al, 2021) at an individual level, the impact may not be as simple as it seems. Earlier research has identified workplace fun in association with job satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…This helps in creating a positive organizational culture that includes the management’s support of fun activities, creates new fun practices, maintains trust, and ensures creative work [ 87 ]. Furthermore, trust can play a significant role in the relationship between workplace fun and its consequences [ 88 ]. Losing trust among employees could possibly result in negative outcomes when the workplace relationship does not reflect the values of camaraderie or when managers are not perceived as benevolent.…”
Section: Managerial Implicationsmentioning
confidence: 99%